Peran Digital Marketing dan Harga Kompetitif Terhadap Keputusan Berlangganan Indihome - Afan Nurcahyo (UIN Raden Mas Said Surakarta, 2018)
This study aim to determine the role of digital marketing and competitive price to buying decision IndiHome Fiber PT Telekomunikasi Indonesia, Tbk. Datel Wonogiri. Research data was obtained by spreading questionnaires using interval scale by using sample of 100 respondents. This research uses sampling with aksidental sampling method and using multiple linear regression analysis technique. Partial test results indicate that the digital marketing has a significant effect on buying decision, competitive price has a significant effect on buying decision. For simultaneous test, the result shows that variable of digital marketing and competitive price together have significant effect to buying decision. Keywords: digital marketing, competitive price and buying decision